Nanotechnology : Ethical and Social Implications. - Khan, Ahmed S. (Nano and Energy., 2012)
""Perhaps the most useful chapter from an instructor's perspective is the one by Deb Newberry. ... Ms. Newberry has assembled a concise, clear, and well-footnoted introduction to the field of nanotechnology products and the ecology of their effects. ... Dr. Khan's own introductory chapter also belongs in the category of standout. He gives good definitions of the field, provides many well-illustrated examples, and includes about thirty pages of scenarios and case studies involving nanotechnology and social or ethical issues. Case studies are one of the book's strengths overall, because several.